2009
DOI: 10.1177/1078155209351329
|View full text |Cite
|
Sign up to set email alerts
|

Expression of lung resistance protein and multidrug resistance-related protein (MRP1) in pediatric acute lymphoblastic leukemia

Abstract: Multidrug resistance (MDR) is a phenomenon by which cells become resistant to unrelated chemotherapeutic agents. The prognostic value that lung resistance protein (LRP) and multidrug resistance-related protein 1 (MRP1) have in the setting of pediatric acute lymphoblastic leukemia (ALL) is controversial. The aim of this study was to investigate the expression of LRP and MRP1 and effect on clinical outcome and prognosis. The mRNA expression of LRP and MRP1 were analyzed in leukemic blasts of 34 pediatric ALL pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…List et al (1996) demonstrated that LRP overexpression was associated with poorer responses to induction therapy and a trend toward shorter response durations and OS times in a study of 66 patients with AML, whereas Huh et al (2006) showed that LRP mRNA expression was associated with resistance to induction chemotherapy among patients with acute leukemia, MRP1 mRNA expression was associated with poorer 2-year survival rates, and expression of both MRP1 and LRP identified patients with very poor 2-year survival rates. Similar findings were reported from a study of 34 pediatric patients with ALL, with MRP1 and LRP mRNA expression being associated with lower CR rates and poorer 2-year survival rates (El-Sharnouby et al, 2010). Finally, a phase 2 study of gemcitabine and mitoxantrone treatment for patients with AML at first relapse suggested that higher levels of expression of total MRP4 and solute carrier family 29 member 2 were associated with not achieving CR (Advani et al, 2010); high levels of expression of glutathione transferase P (encoded by GSTP1) were also seen.…”
Section: Mdr In Acute Myeloid Leukemia and Other Acutesupporting
confidence: 76%
“…List et al (1996) demonstrated that LRP overexpression was associated with poorer responses to induction therapy and a trend toward shorter response durations and OS times in a study of 66 patients with AML, whereas Huh et al (2006) showed that LRP mRNA expression was associated with resistance to induction chemotherapy among patients with acute leukemia, MRP1 mRNA expression was associated with poorer 2-year survival rates, and expression of both MRP1 and LRP identified patients with very poor 2-year survival rates. Similar findings were reported from a study of 34 pediatric patients with ALL, with MRP1 and LRP mRNA expression being associated with lower CR rates and poorer 2-year survival rates (El-Sharnouby et al, 2010). Finally, a phase 2 study of gemcitabine and mitoxantrone treatment for patients with AML at first relapse suggested that higher levels of expression of total MRP4 and solute carrier family 29 member 2 were associated with not achieving CR (Advani et al, 2010); high levels of expression of glutathione transferase P (encoded by GSTP1) were also seen.…”
Section: Mdr In Acute Myeloid Leukemia and Other Acutesupporting
confidence: 76%
“…Some studies suggest a lack of any relationship between mRNA expression profile and prognosis, 7,27,31 while others indicate that some of these genes may influence prognosis. 1,23,24,[32][33][34][35] In our study, the relationship was more obvious in the case of overexpression of MRD1 and MRP1 at mRNA levels. The discrepancy in results may be caused by temporal and local factors (the environmental risk factors of cancer), as well as genetic and hereditary characteristics.…”
Section: Discussionmentioning
confidence: 64%
“…Research has also focused on MRP1 and LRP expression, however, unlike with MDR1 [46], there has not yet been an indication that these have an effect on prognosis, but observed a correlation between MDR1 expression and prognosis [43]. Interestingly, AML cells have been observed to have low expression levels of BCRP/MXR [47].…”
Section: Abc Transporters In Human Cancersmentioning
confidence: 99%